2015
DOI: 10.1155/2015/549818
|View full text |Cite
|
Sign up to set email alerts
|

Species-Related Differences in the Proteome of Rat and Human Pancreatic Beta Cells

Abstract: The core proteomes of human and rat pancreatic beta cells were compared by label-free LC-MS/MS: this resulted in quantification of relative molar abundances of 707 proteins belonging to functional pathways of intermediary metabolism, protein synthesis, and cytoskeleton. Relative molar abundances were conserved both within and between pathways enabling the selection of a housekeeping network for geometric normalization and the analysis of potentially relevant differential expressions. Human beta cells differed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The documented insulin expression and secretion of NT-3 cells warrants evaluation as a potential model for human pancreatic beta cells. Until now, no such human model exists and most basic diabetes research has been performed in a rat insulinoma cell line (INS1E), with obvious limitations such as differences in protein expression and functional status between human and rodent islet cells (34,35). The only human cell line derived from an insulinoma (called CM) has already lost insulin expression and secretion during in vitro culture (36).…”
Section: Discussionmentioning
confidence: 99%
“…The documented insulin expression and secretion of NT-3 cells warrants evaluation as a potential model for human pancreatic beta cells. Until now, no such human model exists and most basic diabetes research has been performed in a rat insulinoma cell line (INS1E), with obvious limitations such as differences in protein expression and functional status between human and rodent islet cells (34,35). The only human cell line derived from an insulinoma (called CM) has already lost insulin expression and secretion during in vitro culture (36).…”
Section: Discussionmentioning
confidence: 99%
“…All experiments were performed in human pancreatic islets and the human insulinproducing cell line EndoC-βH1 [24], increasing their translational potential [25][26][27][28]. The data obtained indicate that IFNα is a crucial mediator of excessive inflammation and ER stress in the early steps of type 1 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…34 Previous reports showed that expression of lysosomal enzymes (MDH1, PC and ACLY) involved in glucose sensing tend to be different in human and rat b cells. 35 A proteome analysis focusing on glucose-responsive insulin production, which is a cellular physiological function specific to human pancreatic b cells, was also reported. The expression increased in Dicer 1 and SLC27A2 under high-glucose conditions.…”
Section: Discussionmentioning
confidence: 99%